2013
DOI: 10.1517/17460441.2013.793668
|View full text |Cite
|
Sign up to set email alerts
|

The discovery and development of prasugrel

Abstract: Prasugrel has a more rapid, more potent antiplatelet effect with less interindividual response variability when compared to clopidogrel. Those therapeutic advantages are attributed to features of its chemical structure that favor the metabolic conversion of prasugrel to its active metabolite. However, the increased risk of bleeding has been associated with a greater antiplatelet effect and dosing profile; this is especially the case in those patients who are at a higher risk of bleeding complications. It is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Prasugrel, a prodrug, (5-[2-cyclopropyl-1-(2-fluorophenyl)-2-oxoethyl]-4,5,6,7-tetrahydrothieno[3,2-c]pyridin-2-yl acetate) is a novel and potent irreversible thienopyridine inhibitor of platelet aggregation [ 26 , 27 ]. Its conformational structure is, like in ticlopidine and clopidogrel, determined by dihedral angles α, β, δ, ε and ζ ( Table 1 , Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prasugrel, a prodrug, (5-[2-cyclopropyl-1-(2-fluorophenyl)-2-oxoethyl]-4,5,6,7-tetrahydrothieno[3,2-c]pyridin-2-yl acetate) is a novel and potent irreversible thienopyridine inhibitor of platelet aggregation [ 26 , 27 ]. Its conformational structure is, like in ticlopidine and clopidogrel, determined by dihedral angles α, β, δ, ε and ζ ( Table 1 , Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 1993, Japanese researchers claimed the patent for a series of hydrothienopyridine derivatives with antithrombotic activity. 78,79 Among these, prasugrel was shown to have a greater antithrombotic effect than clopidogrel. Studies in rodents showed that it had additional properties, such as a longer and more intense effect.…”
Section: Clopidogrel Resistance In Interventional Neuroradiologymentioning
confidence: 99%
“…Studies in rodents showed that it had additional properties, such as a longer and more intense effect. 78 In 2009, the FDA approved prasugrel for use in patients with acute coronary syndrome undergoing percutaneous coronary intervention. 80 Prasugrel is also a prodrug and must be metabolized to be active.…”
Section: Clopidogrel Resistance In Interventional Neuroradiologymentioning
confidence: 99%
See 2 more Smart Citations